Body Contouring in Massive Weight Loss Patients Receiving Venous Thromboembolism Chemoprophylaxis: A Systematic Review. Issue 8 (13th August 2021) - Yin, Christine; McAuliffe, Phoebe B.; Marquez, Jocellie E.; Liao, Christopher D.; Vasilakis, Vasileios; Estrella, Jewel; Labropoulos, Nicos; Khan, Sami U.
Abstract : Background: Venous thromboembolism (VTE) events are the leading cause of morbidity and mortality in plastic surgery. Currently, there is no consensus regarding the use of VTE chemoprophylaxis in the context of the risk for bleeding following specific body contouring procedures. Furthermore, there is increasing popularity of these procedures in the massive weight loss (MWL) patient population, who may be at higher risk due to multiple risk factors. The purpose of this study was to stratify the incidence of VTE and bleeding events among individual, specific body contouring procedures in MWL patients receiving chemoprophylaxis. Methods: A systematic review was designed according to PRISMA guidelines. We screened all articles published between 1988 and 2018 reporting chemoprophylaxis status, VTE, and bleeding events in MWL patients undergoing body contouring procedures. Results: Thirty-one publications were reviewed. The VTE incidence for any procedure was too low to reach significance. Overall, hematoma incidence in single-procedure patients (8.7%) was significantly higher than concomitant-procedure patients (4.2%, P < 0.01). However, when stratified into operative and nonoperative hematomas, no significant difference between single- and concomitant-procedure groups overall was demonstrated for either category. Individually, only thighplasty patients had a higher rate of operative hematomas when undergoing thighplasty alone (5.3%) compared with thighplasty with concomitant procedures (0.6%, P < 0.05). Conclusions: Overall, MWL patients undergoing single body contouring procedures (among abdominoplasty, belt lipectomy, thighplasty) were found to have a higher risk of hematoma compared with those undergoing combined contouring procedures. However, stratified hematoma data revealed no differences in overall risk between single- and multiple-procedure operations.